Tuberculosis incidence, deaths and disability-adjusted life years in children and adolescence, 1990-2021: Results from the Global Burden of Disease Study 2021. - Xue Li; Yuanyuan Li; Liping Guo; Yongyan Chen; Gaobiao Wang; Hanjuan Zhang (PLoS ONE)
Background For a long time, eliminating tuberculosis (TB) has been an enormous challenge in global health. We aim to use the 2021 Global Burden of Disease Study (GBD 2021) to systematically analyze the TB burden in children and adolescents. Methods We used the 2021 GBD to retrieve TB incidence, mortality, and disability-adjusted life years (DALYs) data among people aged 0 to19 years in 204 countries and regions between 1990 to 2021. The data are reported as counts and ratios per 100,000 people and are analyzed by age, sex, location and socio-demographic index (SDI). To quantify the uncertainty of the estimations, we include 95% confidence interval (CI) for each indicator. Results Globally, the TB burden among people under the age of 20 has decreased significantly between 2019 and 2021. The overall incidence of TB among children and adolescents fell by 37.4%, from 2.21(95% UI:1.71-2.76) million in 1990 to 1.38(95% UI:1.06-1.76) million in 2021. Sub-Saharan Africa had the highest increase in TB incidence (302.88, 95% UI: 227.85-385.33). The age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR) and age-standardized DALYs rate (ASDR) of TB in females decreased faster than males. The incidence was higher in children under 5 years old and adolescents aged 15 to 19, showing a bimodal pattern. In addition, mortality caused by multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) have increased dramatically in several areas. The mortality rates for MDR-TB and XDR-TB in Eastern Europe are 0.04(95% UI:0.02-0.05) and 0.02(95% UI:0.01-0.03) respectively. Conclusion Although the burden of TB in children and adolescents has decreased globally, the disease remains a major public health concern, especially in countries with low SDI. To accomplish the ultimate aim of TB elimination, we should continue to invest in TB prevention and control, expand health-care infrastructure construction, and advance TB diagnostic, preventive, and treatment technologies.